133k views
4 votes
What is the solution of the equation? 8d + 2d + 6d + 9 - 6d = 0

2 Answers

3 votes

Answer:

10d + 9 = 0

Explanation:

Simple explanation:

1. 8d + 2d + 6d + 9 - 6d = 0

2. 16d + 9 - 6d = 0

3. Ans: 10d + 9 = 0

Thorough explanation

1. Solve the equation using BIMDAS OR BEDMAS - whatever acronym you were taught

2. Since there are addition and subtraction in this equation we need to solve it from left to right.

3. Re-arrange the equation by putting like terms together - if that makes sense:

So 8d + 2d + 6d + 9 - 6d = 0

Becomes 8d + 2d + 6d - 6d + 9 = 0

4. Then you simply simplify the equation (Remember, go from left to right)

5. (8+2+6)d - 6d + 9 = 0

6. 16d - 6d + 9 = 0

7. (16-6)d + 9 = 0

8. Ans: 10d + 9 = 0

You can leave it at here because you only need to solve the equation. However, if the question says to "solve for d" (which is not the question being asked rn), then take 9 from both sides: 10d + 9 - 9 = 0 - 9

Which gives you: 10d = -9

Then divide by 10

10d/10= -9/10

Ans: d = -9/10

d would equal negative nine over ten

User Patrick Trentin
by
5.2k points
4 votes

Answer:

Explanation:

8d+2d+6d+9-6d = 0

First, combine like terms, so it would become;

10d+9 = 0

Then, separate anything without a variable;

10d = -9

Then you divide;

d= -0.9

User Lahiru Mirihagoda
by
6.5k points